2021
DOI: 10.1001/jamanetworkopen.2020.32101
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Government-Mandated Closures and Restrictions With Aggregate Mobility Trends and SARS-CoV-2 Infections in Nigeria

Abstract: IMPORTANCE To prepare for future coronavirus disease 2019 (COVID-19) waves, Nigerian policy makers need insights into community spread of COVID-19 and changes in rates of infection associated with government-mandated closures and restrictions. OBJECTIVES To measure the association of closures and restrictions with aggregate mobility and the association of mobility with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections and to characterize community spread of COVID-19. DESIGN, SETTING, AND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Isolation or stay at home was an effective measure in reducing the transmission of SARS-CoV-2, but the included studies used results for mobility to assess stay at home or isolation and therefore could have been limited by potential flaws in publicly available phone data, 41 58 102 and variations in the enforcement of public health measures in different states or regions were not assessed. 55 58 102 Quarantine was found to be as effective in reducing the incidence of covid-19 and transmission of SARS-CoV-2, yet variation in testing and case detection in low income environments was substantial. 59 96 98 Another study reported that quarantine was effective in reducing the transmission of SARS-CoV-2 in a cohort with a low prevalence of the virus, yet it is unknown if the same effect would be observed with higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation or stay at home was an effective measure in reducing the transmission of SARS-CoV-2, but the included studies used results for mobility to assess stay at home or isolation and therefore could have been limited by potential flaws in publicly available phone data, 41 58 102 and variations in the enforcement of public health measures in different states or regions were not assessed. 55 58 102 Quarantine was found to be as effective in reducing the incidence of covid-19 and transmission of SARS-CoV-2, yet variation in testing and case detection in low income environments was substantial. 59 96 98 Another study reported that quarantine was effective in reducing the transmission of SARS-CoV-2 in a cohort with a low prevalence of the virus, yet it is unknown if the same effect would be observed with higher prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…November 2020, all the states in the Northeast region faced their first waves of infections, as Figs. S.8-S. 16 show. The social isolation index presented small values, between 38.5% to 40.5% during 2020.…”
Section: Summary For the Northeast Region From May Tomentioning
confidence: 91%
“…As expected, the correlation between the SII and the reproduction number R (t) , as well as the correlation between their daily variations were mainly negative. The estimated median time between a change in SII to imply a change in R (t) in the Southeast region ranged from 15 days (50% CI: [11][12][13][14][15][16][17] in ES to 20 days (50% CI: 20-22) in MG. In both cases, correlation approached zero or became positive basically during periods when SII reached values below 40% or when SII and R (t) stabilized around fixed values.…”
Section: Summary For the Southeast Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S.6 illustrates.The correlation between the daily variations in SII and in the reproduction number R(t) was mainly negative, indicating that, an increase (or decrease) in SII is linked to a decrease (or increase) in R(t). The median time between a change in SII to imply a change in R(t) in the North region ranged from 14 days (50% CI: 12-17) in AC and 22 days (50% CI:[12][13][14][15][16][17][18][19][20][21][22] in AP. Correlation approached zero or became positive basically during periods when SII reached values below 40% or when SII and R(t) stabilized around fixed values.…”
mentioning
confidence: 99%